2019
DOI: 10.1038/s41598-019-51793-7
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Functional Connectivity is Organized as Three Interdependent Gradients

Abstract: The intrinsic functional architecture of the brain supports moment-to-moment maintenance of an internal model of the world. We hypothesized and found three interdependent architectural gradients underlying the organization of intrinsic functional connectivity within the human cerebral cortex. We used resting state fMRI data from two samples of healthy young adults (N’s = 280 and 270) to generate functional connectivity maps of 109 seeds culled from published research, estimated their pairwise similarities, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 148 publications
5
40
0
Order By: Relevance
“…The topography of the dominant principal component of the bipartitions bears strong resemblance to the principal mode of BOLD dynamics observed during high amplitude 'events' (Esfahlani et al 2020), as well as patterns characterized by strong excursions (Betzel et al 2016) or high modularity (Fukushima et al 2018) in time-varying functional connectivity. Similar patterns representing a decoupling of mainly task-positive from task-negative regions have been described and interpreted in previous studies as a major intrinsic/extrinsic dichotomy in functional architecture (Fox et al 2005;Golland et al 2008;Doucet et al 2011;Zhang et al 2019). The pattern reported here is also very highly correlated with cortical gradients (Margulies et al 2016), specifically those derived from eigendecompositions of the functional connectivity matrix.…”
Section: Discussionsupporting
confidence: 88%
“…The topography of the dominant principal component of the bipartitions bears strong resemblance to the principal mode of BOLD dynamics observed during high amplitude 'events' (Esfahlani et al 2020), as well as patterns characterized by strong excursions (Betzel et al 2016) or high modularity (Fukushima et al 2018) in time-varying functional connectivity. Similar patterns representing a decoupling of mainly task-positive from task-negative regions have been described and interpreted in previous studies as a major intrinsic/extrinsic dichotomy in functional architecture (Fox et al 2005;Golland et al 2008;Doucet et al 2011;Zhang et al 2019). The pattern reported here is also very highly correlated with cortical gradients (Margulies et al 2016), specifically those derived from eigendecompositions of the functional connectivity matrix.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, there have been studies linking cytoarchitecture to macroscale neuroimaging data for informing cortical gradient mapping ( Huntenburg et al, 2018 ; Paquola et al, 2019 ), as well as seeing how conditions such as ischemic stroke affect the gradients within the embedding space ( Bayrak et al, 2019 ). Zhang et al constructed intrinsic connectivity maps using network motifs reported in the literature with MDS to create a low-dimensional embedding, identifying three gradients across external-internal, modulation-representation, and anatomical centrality features ( Zhang et al, 2019 ). Recently, Bethlehem et al (2020) investigated how the functional communities in their diffusion map embedding space change across age using a novel dispersion metric.…”
Section: Discussionmentioning
confidence: 99%
“…This spatiotemporal organization is exactly the one mandated by hierarchical generative models. Networks that occupy higher levels may continuously generate predictions to suppress prediction errors of lower brain networks, such as primary sensory and motor regions -which may be engaged when prediction errors cannot be readily cancelled out and disengaged otherwise [93,96,97]. Furthermore, task-specific generative architectures can be formed by selectively engaging and disengaging network elements.…”
Section: Connectivity Patterns As Priorsmentioning
confidence: 99%